De normalistas a bancárias: Caminhos da profissionalização das mulheres no sul do Brasil (1960-1980) - Carlos Geroleti, Luciana (2018)
This article, resulting from a Masters in History, deals with the paths traveled by five women in two professions: the normalist and the banking. Using the Oral History methodology, the research was based on interviews with women who changed the profession of teacher for a career in public banks between the 1960s and 1980s. As it turned out, the change of profession was part of a broader historical process which led many women from the middle classes in Brazil to the labor market, revealing permanences regarding the traditional female occupations